Empowering parents: Understanding adolescents' psychological development through the psychoeducation program "Mengenal Remajaku" - Fitri Ariyanti Abidin; Shally Novita; Kustimah Kustimah; Anggit Sukmawati; Syipa Fadilah (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Adolescents experience abrupt physical and psychological changes. These changes impacted adolescent behavior and the way adolescents respond to their environment. If parents do not understand the changes that occur in their adolescents, parents can experience difficulties in applying their parenting and eventually will impact the quality of the parent-child relationship. Parents need to be educated to understand the characteristics of adolescent development. Therefore, an Online workshop that aims to provide an understanding of the characteristics of adolescent development was conducted. The participant of this online workshop are parents who have adolescents. They were 26 parents aged 35-44 years (average 40.13 years) which were dominated by mothers (92.31%). This three-hour program used the online-zoom platform. It consists of lectures, question and answers session, small group discussions, and making an action plan to be implemented in relation to their adolescents. The results of the reaction evaluation showed that the participants perceived the program as interesting, fun, and useful. The material presented is considered good and applicable in accordance with the conditions of youth and the environment.